Awareness, usage and perceptions of authorship guidelines: an international survey of biomedical authors - Sara Schroter; Tobias Kurth; Ilaria Montagni; M Eikermann; Elke Schäffner (BMJ Open)
Objectives To investigate authors’ awareness and use of authorship guidelines, and to assess their perceptions of the fairness of authorship decisions.Design A cross-sectional online survey.Setting and participants Corresponding authors of research papers submitted in 2014 to 18 BMJ journals.Results 3859/12 646 (31%) researchers responded. They worked in 93 countries and varied in research experience. Of these, 1326 (34%) reported their institution had an authorship policy providing criteria for authorship; 2871 (74%) were ‘very familiar’ with the International Committee of Medical Journal Editors’ authorship criteria and 3358 (87%) reported that guidelines were beneficial when preparing manuscripts. Furthermore, 2609 (68%) reported that their use was ‘sometimes’ or ‘frequently’ encouraged in their research setting. However, 2859 respondents (74%) reported that they had been involved in a study at least once where someone was added as an author who had not contributed substantially (honorary authorship), and 1305 (34%) where someone was not listed as an author but had contributed substantially (ghost authorship). Only 740 (19%) reported that they had never experienced either honorary or ghost authorship; 1115 (29%) reported that they had experienced both at least once. There was no clear pattern in experience of authorship misappropriation by continent. For their last coauthored article, 2187 (57%) reported that explicit authorship criteria had been used to determine eligibility, and 3088 (80%) felt that the decision made was fair. When institutions frequently encouraged use of authorship guidelines, authorship eligibility was more likely to be discussed early (817 of 1410, 58%) and perceived as fairer (1273 of 1410, 90%) compared with infrequent encouragement (974 of 2449, 40%, and 1891 of 2449, 74%).Conclusions Despite a high level of awareness of authorship guidelines and criteria, these are not so widely used; more explicit encouragement of their use by institutions may result in more favourable use of guidelines by authors.